MUDANÇA ESTRATÉGICA E PROCESSO DE INSTITUCIONALIZAÇÃO EM UMA UNIVERSIDADE: O DESENVOLVIMENTO DE ESQUEMAS INTERPRETATIVOS ENTRE OS GESTORES - Fernando Colares Palacios (Universidade Federal de Santa Catarina, 2014)
The objective of the research was to identify and analyze ide as, values and beliefs present in the cognitive processes of the managers of a new university unit deployment of a new strategy. From questions about the dimensions of change proposed by Mintzberg et al.. (2006), is rated the development of interpretive sc hemes able to prove the beginning of a process of institutionalization or not . The data was collected by means of semi - structured interviews with mid-level managers, non - participant observation and document analysis . The research is characterized as a case study with prospect of cross - examination and descriptive qualitative approach, with the focus on the process of strategic change in a brazilian public university The results highlighted the importance of analyzing the interpretive schemes of the lea ders to understand the level of institutionalization of the given project. Also found inconsistent practices with the design of the new unit and that can compromise the effective implementation of the formulated strategy.